Using BIM to optimise and assess the energy efficiency category of SBToolPT-H - Carvalho, José Pedro Almeida (2019)
The current method for assessing the two indicators of the Energy Efficiency category of the Building Sustainability Assessment method SBToolPT-H (P7: Primary energy, P8: In-situ energy production from renewables) is rather time-consuming. The assessment requires many values that need to be calculated manually or with specific spreadsheets, whenever a design is proposed. When a design alteration is introduced, the whole process needs to be repeated, which leads to designers to be discouraged to develop this task. This research explores the use of the Building Information Modelling (BIM) software ? Autodesk Revit and Autodesk Green Building Studio (GBS) ? to assess the Energy Efficiency category. The purpose is to find a more efficient assessing method, encouraging and supporting designers to optimise their projects. More efficient methods can contribute to more sustainable constructions and to decrease the construction industry?s environmental impact. To explore if Revit and GBS can streamline the assessment of this SBToolPT-H category, a case study was carried out. A reference building was created which complied with all the current Portuguese regulations. The reference building was then modelled in Revit and submitted to an energy analysis using GBS. The results showed for indicator P7, that the use of GBS and Revit streamlines the assessment by faster extraction of information thanks to the 3D-model and the energy analysis software. However, the assessment could be made even more efficient if the software and national regulations were more matched such as conformity of units and analysed parameters. Concerning indicator P8, the results showed clearly that using GBS is a rather efficient process.